Basic Concepts of Making Career Decisions in Surah Ar-Ra'd - Sabarrudin, Sabarrudin; Masril, Masril (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Career guidance and counselling is one aspect of guidance. Career orientation is intended so that a person can work well, willingly and diligently and requires job requirements or positions following the person concerned. There are several stages involved in the implementation of career guidance, one of which is career selection. Of course, when making career decisions, different theories of career choice are needed so that the decisions made by an individual match the individual's abilities, aptitudes, and interests. The purpose of this research is when individuals will begin to study the world of work closely and make the right decisions. This article is an alternative solution to the problem of decision theory so that later a person will not regret choosing a career and entering the world of work. This research is library research conducted by collecting information and data from various sources in the library, which is related to the problem to be solved. The data that has been obtained will be analyzed using content analysis. The results of this study indicate that the basic concept of career decision-making in surah Ar-Ra'd verse 11 is in line with career decision-making according to the Miller-Tiedeman lifecareer theory of career decision-making in the process of career guidance and counselling based on the results of the client's own decisions.